The Role of Context in Understanding Misogyny Hadith: A Pragmatic Study - Mia Mutmainah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
Hadith as a source of reference for Islamic law is widely considered to discredit women. These hadiths are then referred to as misogyny hadiths. One of the hadiths that are considered misogyny is the hadith that says that the inhabitants of hell are dominated by women. The hadith is a valid hadith so it needs an in-depth study of the contextual meaning of the hadith. This study is aimed at analyzing the aspects and role of context in understanding the hadith. The analysis of context that had been carried out in this paper refers to the context aspect in the study of Pragmatics. From this context analysis, the contextual meaning of the hadith is generated. This research paper used a qualitative research method. The results of the study show that the aspects of the context behind the hadith are aspects of the speaker, the listener, and the speech situation. Thus, the contextual meaning of the hadith which states that the massive number of the inhabitants of hell are dominated by women is that the hadith is a form of warning and advice to women at that time, namely the people of Medina who often disbelieved in favors and gossip their husbands. That is, the hadith is very contextual so that it cannot only be understood textually.